Money capital new monetary principles for a more prosperous society - Bolton, Patrick 1957-; Huang, Haizhou (Princeton University Press, 2024)
A conventional economic theory, monetarism, holds that inflation is a monetary phenomenon driven by changes in the supply of money. Yet recent experience including the aftermath of the financial crisis of 2008 and the economic development of China contradict this basic prediction. In this book, leading economists Patrick Bolton and Haizhou Huang offer a novel perspective, viewing monetary economics through the lens of corporate finance. They propose a richer theory, where money can be seen as the equity capital of a nation, playing a similar role as stocks for a company. This innovative framework integrates the real and monetary sides of the economy, with a banking sector and debt at its core. In the financial world, companies issue new shares only if it results in some kind of value creation; this is a basic principle of corporate finance that Bolton and Huang argue can be applied to monetary economics. When the government increases the money supply to finance positive net value investments when it prints money to keep the economy going it increases output, not inflation. This is evidenced by the strong growth in GDP and money in China over the last four decades, and in the United States during World War II. The effect of increasing money supply, they argue, depends on how money enters the system and what the money buys. The principles outlined by Bolton and Huang shed new light on a range of issues, including inflation, monetary and fiscal policy, central banking, money and growth, and the international monetary system."